Analisis Tingkat Kebisingan Di Kawasan Bandara Internasional Sultan Syarif Kasim II Pekanbaru - Komang, Rudhi Andreas; Sasmita, Aryo; Andrio, David (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Sultan Syarif Kasim II International Airport Pekanbaru serve domestic and international flights, this airport is also a home base for Squadron 16 and Squadron 12 Roesmin Nurjadin air base. The noise level is affected by flight activity in the airport. The purpose of this research is to determine the intensity of noise at the airport and the surrounding residential area, duration of noise exposure, and mapping of noise spread pattern. Noise measurement method based on KepMenLH No 48 of 1996, and the device used is Sound Level Meter (SLM). Measurement of sound pressure level (Lp) lasted 1 day. Based on the results of data processing of the 5 points of measurement, results showed the level of noise in the airport area is 77.72 to 91.82 dBA . Noise control can be performed by making of noise barriers and using noise-absorbing materials in the construction of houses.Keyword : noise, airport, sultansyarifkasimII